2021
DOI: 10.1007/s00296-021-05056-2
|View full text |Cite
|
Sign up to set email alerts
|

The incidence, clinical characteristics, and outcome of COVID-19 in a prospectively followed cohort of patients with Behçet’s syndrome

Abstract: Initial case series of small number of patients at the beginning of the pandemic reported a rather guarded prognosis for Behçet's syndrome (BS) patients infected with SARS-CoV-2. In this prospective study, we describe the incidence, clinical characteristics, disease course, management, and outcome in a large cohort of BS patients with laboratory-confirmed infection of SARS-CoV-2. We defined a cohort of 1047 registered BS patients who were aged between 16 and 60 years and seen routinely before the pandemic at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 57 publications
2
7
0
Order By: Relevance
“…In line with our findings, a Turkish prospective cohort study in patients with BD found an increased infection rate compared to the general Turkish population (26). Ozcifci et al showed a cumulative incidence of COVID-19 in the BD patient group of 20.5%, in the Turkish general population the cumulative incidence of COVID-19 was 5.77% (26). Four patients, one male and three female, in our cohort were admitted because of severe symptomatic COV-ID-19 infection.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with our findings, a Turkish prospective cohort study in patients with BD found an increased infection rate compared to the general Turkish population (26). Ozcifci et al showed a cumulative incidence of COVID-19 in the BD patient group of 20.5%, in the Turkish general population the cumulative incidence of COVID-19 was 5.77% (26). Four patients, one male and three female, in our cohort were admitted because of severe symptomatic COV-ID-19 infection.…”
Section: Discussionsupporting
confidence: 92%
“…In Table IV we present an overview of the current literature on BD and COV-ID-19. We have added 4 studies which also used a sample survey (23)(24)(25)(26). In total 2014 BD patients were discussed in these studies, 313 patients were tested positive.…”
Section: Discussionmentioning
confidence: 99%
“…Skin hypersensitivity and the induction of systemic symptoms in response to streptococcal antigens, as well as significant inflammatory reactions to polysaccharide pneumococcal vaccine in BS are well known [ 38 – 41 ]. Moreover, we observed very recently that 36 of 214 (16.8%) patients with BS experienced a flare during COVID-19 infection [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of IFNα inhalation was reported in patients with various comorbidities and conditions, including patients with atopic dermatitis, [38] allergic rhinitis, [38] bronchiolitis, [25] chronic obstructive pulmonary disease, [84] , [162] tuberculosis, [55] cardiovascular disease, [22] hypertension, [22] , [84] , [150] , [162] diabetes, [32] , [39] hyperlipidemia, [150] obesity, [126] metabolic syndrome, [192] chronic hepatitis B infection, [76] , [153] chronic kidney disease, [22] , [70] malignancy, [163] liver transplant, [50] kidney transplant, [70] , [172] and pregnancy. [19] The use of subcutaneous injection of IFNα was reported in patients with diabetes, [42] hypertension, [42] , [44] hyperlipidemia, 42 chronic hepatitis B infection, [140] primary myelofibrosis with macrocytic anemia, [44] dementia, [44] chronic kidney disease, [44] Behcet's disease, [190] and osteoporosis. [44] However, whether IFNα treatment is safe and efficacious in COVID-19 patients with these comorbidities requires further clinical studies.…”
Section: Comprehensive Review Of the Literature On The Safety And Efficacy Of Interferon Alpha Treatment In Covid-19 Patientsmentioning
confidence: 99%
“…Another piece of evidence came from the observation of patients with Behcet’s syndrome in Turkey. [190] Behcet’s syndrome is a rare inflammatory disorder that results in a wide range of signs and symptoms and can be treated with IFNα. Using univariate logistic regression, the researchers analyzed data from 1,037 patients and found that patients on IFNα treatment had an odds ratio of 0.12, meaning that they were 88% less likely to contract COVID-19 disease.…”
Section: Interferon Alpha Treatment For Covid-19 Patients In the Current Contextmentioning
confidence: 99%